2023
DOI: 10.21203/rs.3.rs-1587034/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Distinct Clinical Phenotypes of Cardiogenic Shock Using Machine Learning Consensus Clustering Approach

Abstract: Background Cardiogenic shock (CS) is a complex state with many underlying causes and associated outcomes. It is still difficult to differentiate between various CS phenotypes. We investigated if the CS phenotypes with distinctive clinical profiles and prognoses might be found using the machine learning (ML) consensus clustering approach. Methods The current study included patients who were diagnosed with CS at the time of admission from the electronic ICU (eICU) Collaborative Research Database. Among 21,925 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…The model incorporated 13 laboratory parameters (calcium, carbon dioxide, creatinine, creatine kinase-MB, HGB, glucose, mean corpuscular volume [MCV], mean corpuscular HGB concentration, platelets, potassium, RDW, sodium, and leukocytes) to forecast disease severity and mortality, revealing a nonlinear correlation between calcium and HGB and post-infarction mortality in patients. Wang et al 98 employed unsupervised ML consensus clustering techniques, primarily incorporating the following parameters: blood pressure (systolic, mean, and diastolic), renal function (creatinine, blood urea nitrogen, and estimated glomerular filtration rate), electrolytes and acid-base compounds (potassium and bicarbonate), liver function (albumin), indicators related to red blood cells (red blood cell count and red cell distribution width), as well as various scoring systems (SOFA, APS III, and APACHE IV) for the prediction and evaluation of cardiogenic shock. In exploring the best predictive model for heart failure, Li et al 50 assessed seven ML algorithms and identified XGBoost as the superior algorithm.…”
Section: Study Of Ai Application In Diagnosis Of Cvdmentioning
confidence: 99%
“…The model incorporated 13 laboratory parameters (calcium, carbon dioxide, creatinine, creatine kinase-MB, HGB, glucose, mean corpuscular volume [MCV], mean corpuscular HGB concentration, platelets, potassium, RDW, sodium, and leukocytes) to forecast disease severity and mortality, revealing a nonlinear correlation between calcium and HGB and post-infarction mortality in patients. Wang et al 98 employed unsupervised ML consensus clustering techniques, primarily incorporating the following parameters: blood pressure (systolic, mean, and diastolic), renal function (creatinine, blood urea nitrogen, and estimated glomerular filtration rate), electrolytes and acid-base compounds (potassium and bicarbonate), liver function (albumin), indicators related to red blood cells (red blood cell count and red cell distribution width), as well as various scoring systems (SOFA, APS III, and APACHE IV) for the prediction and evaluation of cardiogenic shock. In exploring the best predictive model for heart failure, Li et al 50 assessed seven ML algorithms and identified XGBoost as the superior algorithm.…”
Section: Study Of Ai Application In Diagnosis Of Cvdmentioning
confidence: 99%